Backyard poultry farming with Vanaraja and Srinidhi: proven technology for doubling the tribal farmers’ income in Nagaland - Singh, Mahak; Mollier, R. Talimoa; G., Rajesha; Nguillie, A. Myngthungo; Rajkhowa, D. J.; Rajkumar, U.; Paswan, Chandan; Chatterjee, R. N. (Indian Farming, 2018)
The eggs and meat of birds reared in the backyard farming fetches higher premium due to high consumer acceptability even in the urban sectors where plenty of eggs and poultry meat from commercial units are available. Besides stable supply of high-quality animal food, backyard poultry production promotes income opportunities particularly for the weaker sections in the tribal areas. The backyard farming will certainly improve the economic status of a majority of rural/tribal families from lower socio-economic groups in the rural/tribal areas. Backyard farming fulfill a wide range of functions e.g. the provision of meat and eggs, food for special festivals, chicken for traditional ceremonies, pest control and petty cash, utilizing minimum inputs, minimum human attention, and causing less environmental pollution. It can be concluded that backyard poultry farming with Vanaraja and Srinidhi varieties is a proven technology for doubling the farming income in tribal areas particularly in Nagaland.